2014
DOI: 10.1093/jnci/dju055
|View full text |Cite
|
Sign up to set email alerts
|

US Incidence of Breast Cancer Subtypes Defined by Joint Hormone Receptor and HER2 Status

Abstract: In the future, SEER data can be used to monitor clinical outcomes in women diagnosed with different molecular subtypes of breast cancer for a large portion (approximately 28%) of the US population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
832
4
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,090 publications
(931 citation statements)
references
References 26 publications
47
832
4
11
Order By: Relevance
“…2,3,14,35 The data presented here are in accordance with the recently published US Surveillance, Epidemiology, and End Results (SEER) registry data, and with data from the UK and Canada that showed HER2 positivity rates of 14.5-15.0% in large patient cohorts. 28,36,37 Therefore, our study reflects published and realistic expectations of HER2 positivity rates in pathology institutes today.…”
Section: Er-negative/ Pgr-negativesupporting
confidence: 69%
“…2,3,14,35 The data presented here are in accordance with the recently published US Surveillance, Epidemiology, and End Results (SEER) registry data, and with data from the UK and Canada that showed HER2 positivity rates of 14.5-15.0% in large patient cohorts. 28,36,37 Therefore, our study reflects published and realistic expectations of HER2 positivity rates in pathology institutes today.…”
Section: Er-negative/ Pgr-negativesupporting
confidence: 69%
“…To study the clinical, demographic, and socioeconomic differences within Luminal A (HR+/HER2−) and Luminal B (HR+/HER2+) clinical breast cancer subtypes, we gathered 134,639 patients with HR+ and known HER2 receptor status from the SEER database 6. Among these patients, 118,285 (87.8%) cases were HR+/HER2− (Luminal A) (Table 1) and 16,354 (12.2%) were HR+/HER2+ (Luminal B) tumors (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Across breast cancer subtypes, there exist demographic and socioeconomic status (SES) differences 6. Previous reports have found that differences in SES may reflect underlying differences in exposures to known breast cancer risk factors, as women with higher SES tended to have lower parity and more frequent use of exogenous hormones 7, 8, 9.…”
Section: Introductionmentioning
confidence: 99%
“…(17) 22 (17) 16 (19) 3 (8) 6 (24) pT2 137 (50) 64 (49) 44 (54) 16 (41) 13 (52) pT3 22 (8) 11 (9) 7 (9) 3 (8) 1 (4) pT4 70 (25) 33 (25) 15 (18) 17 (43) Tumors were grouped into four major subclasses, based on the receptor status as follows: Hormone receptor (HR) positive HER2 negative (HR+/HER-), HR negative and HER2 positive (HR-/HER2+), HR positive and HER2 positive (HR+/HER2+), and the TNBCs (HR-/ HER2-). 43 of the 645 patients had an initial HER2 status assessed as equivocal, but were not tested further to unambiguously assess the status of HER2.…”
Section: Resultsmentioning
confidence: 99%